2013
DOI: 10.4021/gr533e
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter Pylori Infection in a Group of Egyptian Children With Upper Gastro-Intestinal Bleeding

Abstract: BackgroundUpper gastrointestinal bleeding is a life threatening condition in children. Common sources of upper gastrointestinal bleeding in children include mucosal lesions and variceal hemorrhage. Helicobacter pylori (H. pylori) is a Gram negative spiral-shaped bacterium that is found in the gastric mucous layer or adherent to the epithelial lining of the stomach. It causes more than 90% of duodenal ulcers and up to 70-80% of gastric ulcers. The relationship between H. pylori infection and upper GIT bleeding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…The prevalence rate was 54% among symptomatic children, and it compares to the rates in the literature from other Arab countries. [21][22][23][24] Table 7 summarizes these histology-based studies. Jordan's high prevalence rate is similar to those of Egypt and Saudi Arabia and almost double those of Oman and Kuwait.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence rate was 54% among symptomatic children, and it compares to the rates in the literature from other Arab countries. [21][22][23][24] Table 7 summarizes these histology-based studies. Jordan's high prevalence rate is similar to those of Egypt and Saudi Arabia and almost double those of Oman and Kuwait.…”
Section: Discussionmentioning
confidence: 99%
“…Studies from Kuwait, Saudi Arabia, Egypt, and Oman showed the prevalence of H. pylori to be 31%, 62%, 65% and 25 %, respectively. [21][22][23][24] In Jordan, studies estimated the HBP of H. pylori in adults to be 68%-82%, 7,25,26 and the presence of H. pylori infection was documented in 50-79% of gastric cancer biopsies in adult Jordanians. 27,28 Serology -based studies in asthmatic and healthy Jordanian children estimated H. pylori prevalence to range from 18.1% to 55.5%, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…El-Mazary et al investigated the presence of H. pylori in Egyptian children who presented with non-variceal upper gastrointestinal bleeding. They reported a prevalence rate of 65% [39]. Another study from Oman documented the overall prevalence of biopsy proven H. pylori infection at 25% [13].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the scarce data regarding H. pylori in Middle Eastern children, a cohort study conducted in Oman in 2014 showed an overall prevalence of biopsy-diagnosed H. pylori infection of about 25% [13]. Additionally, data collected in Egypt and Saudi Arabia showed prevalence levels of 65% and 62%, respectively [14,15]. As for local evidence, a study of dyspeptic children conducted in Northern Jordan revealed an 82% prevalence based on histologic evidence [16].…”
Section: Introductionmentioning
confidence: 99%